Organization and development of the vegetation on the dump «Livoberezhny» (Ecological Bulletin of Kryvyi Rih District, 2019)
The speciﬁcity of the organization and peculiarities of the development of vegetation of technogenic ecotopes are considered. The taxonomic, ecological and arealic composition of groups of plants of the dump of «Livoberezhny» of the Kryvbas is determined. The analysis of methods of distribution and estimation of economic value of the types of serial plant communities in the research area is carried out.
Keywords: plant groups; dump; development; dynamics; organization; composition